Implementation process of the Surgical Safety Checklist: integrative review - Maria Fernanda do Prado Tostes; Cristina Maria Galvão (Universidade de São Paulo, 2019)
ABSTRACT Objective: to analyze the evidence available in the literature on the process of implementing the Surgical Safety Checklist, proposed by the World Health Organization, in the practice of health services. Method: integrative review, the search for primary studies was performed in three relevant databases in the health area, and the sample consisted of 27 studies, which were grouped into three categories. Results: the synthesis of the evidence indicated the different strategies that can be adopted in the implementation process (introduction and optimization) of the Surgical Safety Checklist, and the facilitators and barriers that determine the success in using this tool. Conclusion: in health services, implementing the checklist is a complex and challenging process that requires effective leadership, clear delegation of responsibilities from each professional, collaboration between team members, and institutional support. The synthesis of the generated knowledge can assist nurses in decision making, especially in identifying strategies for the effective implementation of the Surgical Safety Checklist, since nursing has the potential to be a protagonist in the planning and implementation of best practices for patient safety.